Robust H∞ Controller Design for Active Vibration Suppression with Input Constraints - El Heraiki, Sara; Tacal, Buse; Ucun, Levent (IEEE, 2019)
This study deals with robust H-infinity controller design for active vibration suppresion system where the input constraints are taken into consideration in addition to model uncertainties that are present in the system model. Two different approaches are utilized in order to implement the input constraints into the controller design process. The robust H-infinity controller design algorithms involving input constraints are carried out via linear matrix inequalities and the performance of obtained controllers is illustrated in simulation studies where a two-story structure supplied with an Active-Mass-Damper(AMD) is used.
Keywords: Robust control; H-infinity dynamic output feedback controller; input constraint; vibration suspension; OUTPUT-FEEDBACK CONTROL; Automation & Control Systems